Percepções de pais de filhos com transtorno do espectro autista sobre o impacto nas ocupações paternas - Rezende, Vanessa da Costa (2023)
The daily care of a child with Autistic Spectrum Disorder (ASD) brings significant changes in the daily life of a family in need of adaptations in the roles of its members and attitudes towards a new lifestyle. Research related to paternal occupations has not yet been so explored compared to studies with mothers when it comes to a child with ASD. This study aims to identify parents' perceptions about the impact of daily care for their children with ASD on their occupations. This is a descriptive-exploratory and quali-quantitative research. Participants are parents of children diagnosed with ASD who agreed to participate in the research in accordance with ethical procedures. Data collection took place exclusively through the Google Forms questionnaire, addressed to the father, which addressed questions related to activities carried out in daily life with their child with ASD and their relationships with other paternal occupations. The sample was composed of 28 participants. The sample was characterized by parents with an average age of 41 years old, most of them are married and live with their wives and their child (ren) with ASD. They have completed high school and have paid professional activity. Most of their children are boys, between the ages of 3 and 6, who attend school and receive care from specialized professionals. The results indicate that the father makes changes in his work occupations due to the daily life with his son with ASD and demonstrate restrictions in study and leisure occupations. They recognize the mother's participation as the majority however they participate and are aware of what happens to their child. The exploratory analysis verified the confirmation of four of the 16 hypotheses tested: (1 and 2) the higher the father's education level, the greater the frequency of rehabilitation services in the private network and the frequency of the child with ASD in school private. (3) Parents who practiced religious activities frequently declared greater presence in the responsibilities of domestic activities. And finally (4), it was confirmed that parents who practiced religious activities frequently and with higher education, filled out the open space of the questionnaire expressing feelings, pain, beliefs, emotions and sharing facts and challenges of their daily lives. It is suggested that future research explore the investigated variables, plus others (for example, the severity of the symptom of the child with ASD, the number of children, size of the support network) with a greater number of participants in the perspective of demonstrating, further, the needs of the father with the child with ASD and developing support for him.